Labour market integration of refugees and the importance of the neighbourhood: Norwegian quasi-experimental evidence - Henrik L. Andersen; Liv Osland; Meng Le Zhang (Journal for Labour Market Research, 2023)
This paper exploits a quasi-experimental feature of the Norwegian spatial dispersal policy for UNHCR quota refugees, which leads to nearly as-if random initial residential settlement of the refugees. In this framework, we study if there are positive long-run employment consequences of being assigned to neighbourhoods with higher residential labour force participation rates. Our results show a positive and statistically significant relationship between the initial neighbourhood participation rates and refugee labour market outcomes, but these overall effects are substantively small: A one standard deviation higher participation rate in the initial neighbourhood is associated with an 1.2%-point increase in the refugees' later employment probability. However, our subgroup analysis shows substantial effects around 2.6%-points for men older than 25 years at the time of entry to Norway. In comparison, the point estimates for women and persons younger than 25 years at the time of arrival are close to zero and statistically insignificant.
Keywords: J15; J18; R23; 330; Refugee employment; Settlement policy; Neighbourhood; Quasi-experimental; Administrative data